INITIAL L2C MULTIPATH AND NOISE PERFORMANCE ANALYSIS FROM REAL DATA - FARRET, JULIO CESAR; CARVALHO DOS SANTOS, MARCELO; SUKEOVA, LILIANA (Boletim de Ciências Geodésicas, 2010)
The modernization of the Global Positioning System has become already a reality with the launching of the first modern satellites. The new L2C signal has potential to provide additional information beyond the existing signals such as in environments with obstructions (urban areas, canyons, and forests). Obviously, questions arise. What is the evolution in terms of performance, user facilities and positional quality that this new signal will bring to civilian users? Will there be improvements over the old challenges experienced by the legacy signal, such as the ionospheric error and multipath? With the launch of the first satellites broadcasting the new L2C signal the possibility for an analysis of the behaviour of this signal under multipath and noise making use of actual observations became a reality. Multipath and noise double-difference residuals were extracted from L2C phase and code pseudorange, as well as from the existing C/A code in the L1 carrier for comparative analysis. The daily repeatability of these signals has been investigated aiming to extract and to separate the multipath and noise. Preliminary results confirm slightly smaller multipath values in the L2C signal.